THE IGNALINA NUCLEAR POWER PLANT AND THE ENVIRONMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Lithuania has to solve a lot of problems when closing Ignalina nuclear power plant (INPP). One of them is predicting, monitoring and managing of radiation situation and its impact to environment during this period. Calculated data files for nuclides in nuclear fuel could be used for this aim.This work presents our calculations of concentrations and activities of actinides and fission products in RBMK-1500 reactor fuel in dependence on fuel burn up and cooling time.Calculations were made using French computer code Apollo1 [1].